2011
DOI: 10.1142/s1793292011002457
|View full text |Cite
|
Sign up to set email alerts
|

THE ADVANTAGE OF LOW GROWTH TEMPERATURE AND V/III RATIO FOR InxGa1-xAs NANOWIRES GROWTH

Abstract: Cylindrical In x Ga 1-x As nanowires (NWs) perpendicular to the substrate have been successfully grown using MOCVD. Morphology of In x Ga 1-x As NWs has been observed using Field Emission-Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy (TEM). Both FE-SEM and TEM results show that the NWs grown at low growth temperature and V/III ratio were via direct impinging mechanism. Energy Dispersive X-ray spectroscopy (EDX) results confirm that the cylindrical NWs grown via direct impinging mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, it is assumed that the addition of x may also cause the changing in NWs growth mechanism. At the low indium mole fraction, the NWs grew via direct impinging mechanism therefore the NWs tend to has uniform diameter [9,10]. Nevertheless, by increasing the indium mole fraction the growth mechanism was changed to the second model (combination of the direct impinging and diffusion of source atoms from surface of substrate) [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is assumed that the addition of x may also cause the changing in NWs growth mechanism. At the low indium mole fraction, the NWs grew via direct impinging mechanism therefore the NWs tend to has uniform diameter [9,10]. Nevertheless, by increasing the indium mole fraction the growth mechanism was changed to the second model (combination of the direct impinging and diffusion of source atoms from surface of substrate) [9].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, In x Ga 1-x As NWs must be grown carefully by optimizing the growth mechanism and controlled the growth condition. These NWs can be grown via direct impinging mechanism; combination of direct impinging and diffusion mechanism from surface of substrate as well as domination of diffusion mechanism from surface of substrate [9,10]. Direct impinging mechanism produces cylindrical NWs with relatively uniform in the distribution of chemical composition [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many factors during nanowire growth increase the complexity of In compositional modulation, including growth temperature, seed and substrate type, solubility of species inside the metallic seed, flow rate, etc. It has been suggested that the ternary nanowires are inclined to form core-shell structure because of the discrepancy of thermal pyrolysis behavior among several organic precursors in terms of VLS and vapor liquid (VL) mechanisms, (Wibowo et al, 2011; Zhang et al, 2015; Qu et al, 2017) which makes research into the influence of composition on properties difficult. Compositional information from different nanowire regions has to be collected with an energy-dispersive X-ray spectroscopy (EDS) by preparing a transmission electron microscope (TEM) cross-sectional sample with focus ion beam (FIB) or ultramicrotome.…”
Section: Introductionmentioning
confidence: 99%